Red blood cell transfusion burden in myelodysplastic syndromes (MDS) with ring Sideroblasts (RS): A retrospective multicenter study by the Groupe Francophone des Myélodysplasies (GFM). Issue 5 (22nd April 2022) - Jouzier, Claire; Cherait, Amina; Cony‐Makhoul, Pascale; Hamel, Jean‐François; Veloso, Melanie; Thepot, Sylvain; Cluzeau, Thomas; Stamatoullas, Aspasia; Garnier, Alice; Guerci‐Bresler, Agnès; Dimicoli‐Salazar, Sophie; Pica, Gian Matteo; et al.
Abstract: Background: MDS‐RS patients are characterized by chronic anemia and a low risk of Acute Myeloid Leukemia (AML) progression and they generally become Red Blood Cell (RBC) transfusion dependent (TD). Study design and methods: We performed a retrospective "real‐life" observational study of 6 months in 100 MDS‐RS TD patients, recruited in 12 French centers, to describe transfusion characteristics, and evaluate the frequency and causes of hospitalizations, health costs, and morbidity, associated with transfusion dependency, in a French population of RBC transfusion‐dependent MDS‐RS patients. Results: 79% of the patients had high transfusion burden (HTB) and 21% low transfusion burden (LTB). HTB patients had a longer disease duration (6 vs. 3.7 years, p  = 0.0078), more frequent iron chelation (82% vs. 50%, p  = 0.0052) and higher serum ferritin ( p  = 0.03). During the 6‐month study period, 22% of the patients required inpatient hospitalization, 36% of them for symptomatic anemia requiring emergency RBC transfusion. The 6‐month median transfusion costs, including the cost of the day care facility, transportation to and from the hospital, iron chelation, and lab tests, was 16, 188€/patient. Discussion: MDS‐RS represents the archetypal type of chronically transfused lower‐risk MDS. Most of those patients have a high transfusion burden and thus frequently need visits to the hospital's day care facility, and frequent hospitalizations, with an overall high median treatment cost. Those costs should be compared with costs of new treatments potentially able to avoid RBC transfusion dependence and to reduce the complications of chronic anemia in MDS‐RS patients.